Pengaruh Ukuran Partikel dan Komposisi Semen- Partikel terhadap Kualitas Papan Semen dari Cangkang Kemiri (Aleurites Moluccana Wild) - Ira Lestari Simbolon; Tit0 Sucipto; Rudi Hartono (Program studi Kehutanan USU, 2015)
The Objective of this reseach were to evaluate partcile size and effect of cement- candle nut shell ratio to cement board quality, and to determine optimum particle size and cementparticle ratio that resulting the best physical and mechanical properties of cement board. The size of board was 25 cm x 25 cm x 1 cm with density target was 1 g/cm3. The ratio of particle size were 30 & 80 mesh, and the cement particle ratio were 80:20, 70:30, 60:40. Magnesium cloride was used as catalys to accelerate hardening process. The physical and mechanical propertis of board was evaluated according to JIS A 5417-1992. The result showed that density, moisture content, water absortion thickness swelling, MOE & MOR were 1.00-1.08 gr/cm3; 7.45-11.56%; 5.28-7.02%; 6.12-7.70%; 1.89-4.40%; 4.34-7.90%; 5176-9158 kg/cm2 dan 45.51-62.08 kg/cm2, respectively. All the physical properties had fulfill standard requirement. Whereas MOR & MOE didn’t fulfilled JIS A 5417-1992. The best treatment in this research was particle size of 30 mesh and particle-cement composition of 80:20. Keywords: cement board, candlenut shell, cement – particle ratio, physical and mechanical properties